Draft genome sequencing data of a pathogenic Pantoea stewartii subspecies stewartii strain SQT1 causing bronzing disease of jackfruit in Malaysia - Ibrahim, Rohaya; Ismail Suhaimy, Noor Wahida; Tan, Shu Qing; Ismail, Siti Izera; Md Yasin, Ina Salwany; Yusof, Mohd Termizi; Awang @ Mansor, Mohd Hakiman; Karam Singh, Daljit Singh; Mohamed Zulperi, Dzarifah (Elsevier, 2020)
A Gram-negative bacterium, Pantoea stewartii subspecies stewartii (P. stewartii subsp. stewartii) has been recognized as the causative agent for jackfruit bronzing disease in Malaysia. Here, we report the whole genome sequencing dataset of P. stewartii subsp. stewartii strain SQT1 isolated from local infected jackfruit. The paired-end libraries with an insert size of 350 bp was subjected to the Illumina Hiseq 4000, generating a genome size of 4,783,993 bp with a G+C content of 53.7%. A total protein of 4,671 was identified including virulence factors, resistance factors and secretion systems. Pantoea stewartii subsp. stewartii strain DC283 (NCBI accession no. CP017581.1) was used as a reference genome, where the query hit 72% coverage and average sequencing depth of 68. In total, 28,717 nucleotide polymorphisms, 520 small insertion/deletions and 142 structure variants were identified. The complete genome was deposited at the European Nucleotide Archive under the sample accession number ERP119356 and study accession number PRJEB36196.